OPERACIÓN CÓNDOR: UNA DÉCADA DE TERRORISMO INTERNACIONAL EN EL CONO SUR JOHN DINGES Traducción de Gabriela Torres Ediciones B, 2004 Santiago de Chile ISBN: 956-7510-96-2 432 páginas - González Jácome, Jorge; Pontificia Universidad Javeriana (2006)
null